Simulation and commissioning of a Faraday cup for absolute charge measurements of very high-energy electrons in-air at PEER - Cayley, James; Paino, Jason; Guatelli, Susanna; Rosenfeld, Anatoly; Lerch, Michael; Tan, Yaw-Ren E. (Frontiers in Physics, 2024)
The PEER beamline at ANSTO Australian Synchrotron comprises a 100 MeV linac injector that is currently being developed for ultra-high dose-rate very high-energy electron radiotherapy research. Previously, dosimetry studies discovered a lack of reliable charge measurement to the in-air end station, though no change in response was recorded in fast current transformer measurements, the only available diagnostic device for measuring charge. This work describes the process of simulating, then commissioning a purpose built Faraday cup to ascertain absolute charge measurements, in-air at PEER. By combining simulation data with experimental results, the PEER Faraday cup is shown to possess a primary electron capture efficiency of (99.22 ± 0.10)%, with a net capture efficiency due to secondary electron emission of (97.87 ± 0.24)%.These results show the PEER Faraday cup performs as intended and when scaled against simulations will be suitable for measuring absolute charge at PEER.